Pengembangan Inovasi Literasi, Numerasi, Administrasi, dan Teknologi di SDN Kertamukti 01 Melalui Program Kampus Mengajar Batch 1 - Hasibuan, Akmal Rizki Gunawan; Mulyadi, Acep; Anjani, Alya Rekha; Lubis, Rabiyannur; Andani, Anggitha Rozinah (Jurnal PGSD, 2022)
The "Teaching Campus" program has only started to be implemented at the end of 2020, where the target is students, especially at the elementary school level. The purpose of this study is to find out literation-numeration learning, technology and administration inovation in the COVID-19 period. This study uses a qualitative descriptive method which is subject to 303 students at SDN Kertamukti 01, Cibitung. Data were collected using documentation and observation techniques. The result showed that COVID-19 pandemic had impact and there were constraints on learning for learners and teachers because learnig is done online. The first program implemented was training on the application of technology for online learning to teachers at SDN Kertamukti 01, such as using the Kahoot, Quizizz and Canva applications. The next program is home-visit teaching and programs in the field of administration, such as the preparation of one-sheet lesson plans, updating school accreditation and making school logos for correspondence and others. With this situation, all remain vigilant and keep themselves in accordance with health protocols recommended by the government to avoid the coronavirus.